Analisis Dalam Pembiayaan Bank Syariah Indonesia Pada Tahun 2020-2022 - Juliani Wulandari; Bunga Aura Putri Sulistyono; Rizky Wahyu Pranata; Renny Oktafia (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
bank Islam Indonesia are the end result of the mixed of 3 Islamic banks, specifically BNI Syariah, BRI Syariah and Mandiri Syariah. The reason of this have a look at is to map the financing situation of Islamic banks in Indonesia. The methodology used in this take a look at is a quantitative method the use of information and time processing strategies. regular. the primary position of Islamic banks is to gather budget from the general public based on the principle of deposit agreements, also referred to as Al-Wadiah agreements. those assets are then made available inside the form of financing. Islamic banking financing consists of Musyarakah, Mudharabah, Ijarah, Murabahah and Istishna.